German Spoken Language Features In Netzwerk A1: A Textbook Analysis - Anisa Rahmawati; Hafdarani; Putrasulung Baginda (Nexus Publishing, 2025)
This study analyzes the representation of spoken language features in Netzwerk A1, a German language textbook used at Universitas Pendidikan Indonesia. Through qualitative descriptive analysis, the research identifies twelve distinct spoken language features, categorized into Dialekt (6.7%), Standardsprache (25%), and Alltagsprache (58.3%). The findings reveal that two-thirds of these features directly support speaking and listening skills development, while one-third contribute indirectly. Notable findings include Chapter 7's focus on informal written communication in social media contexts. The study demonstrates how Netzwerk A1’s incorporation of authentic spoken language features enhances students' exposure to native speaker communication patterns.